Proboscipedia and Sex combs reduced are essential for embryonic labial palpus specification in Bombyx mori - Ru ZHANG; Zhong-jie ZHANG; Ye YU; Yong-ping HUANG; Ai-rong QIAN; An-jiang TAN (Journal of Integrative Agriculture, 2020)
Hox genes of proboscipedia (pb) and Sex combs reduced (Scr) and their cofactors are required for determination of insect mouthpart identity and play important roles in insect organ morphogenesis. However, in the lepidopteran insects, including many agricultural and forest pests, the roles of these genes in determination of mouthpart morphogenesis are unclear. Here we report that both BmPB (Gene ID: 101740380) and BmSCR (Gene ID: 692761) are essential for labial palpus specification in a lepidopteran model insect, the silkworm, Bombyx mori. During embryonic morphogenesis, CRISPR/Cas9-mediated mutagenesis of BmPB induced transformation of labial palpus into thoracic leg and BmSCR mutation transformed labial palpus into maxilla. Mutagenesis of Hox-related cofactor extradenticle (BmEXD; Gene ID: 692478) and its nuclear localization factor homothorax (BmHTH; Gene ID: 576938425) also induced distortion of embryonic labial palpus. Furthermore, mutagenesis of each of the four genes induced severe degeneration of spigot morphogenesis, an important part of spinneret structure. Quantitative real-time PCR analysis further revealed that the transcriptional interaction among these genes. Our data thus provide novel evidence for Hox gene regulation of insect embryonic patterning.